2011
DOI: 10.1007/s10899-011-9275-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Reliability of the Gambling Functional Assessment: Revised

Abstract: Dixon and Johnson (Anal Gambl Behav 1: 44-49, 2007) proposed the Gambling Functional Assessment as a tool to identify the consequences maintaining the respondent's gambling behavior, but subsequent studies on its psychometric properties suggested that it could use improvement. The present study investigated the internal consistency of the Gambling Functional Assessment--Revised using the responses of 1,060 undergraduate students. Temporal reliability was assessed by a second administration of the measure four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…Future research should investigate the process of change within maintaining behavioral functions of video game play. The current findings are consistent with research on other addictive behaviors (e.g., pathological gambling) ( Weatherly, Miller, Montes, & Rost, 2012 ; Weatherly, Miller, & Terrell, 2011 ). Weatherly et al.…”
Section: Discussionsupporting
confidence: 90%
“…Future research should investigate the process of change within maintaining behavioral functions of video game play. The current findings are consistent with research on other addictive behaviors (e.g., pathological gambling) ( Weatherly, Miller, Montes, & Rost, 2012 ; Weatherly, Miller, & Terrell, 2011 ). Weatherly et al.…”
Section: Discussionsupporting
confidence: 90%
“…No items are reverse coded. Research has shown that the internal consistency of the GFA-R is high [10]. GFA-R scores have also been shown to have good temporal reliability ( r = 0.80 at four weeks and r = 0.81 at 12 weeks [10]).…”
Section: Methodsmentioning
confidence: 99%
“…Original research [2] reported that the SOGS had high internal consistency ( α = 0.97), and subsequent research has reported that it has fair ( α = 0.69, [17]) to good ( α = 0.81, [20]) internal consistency. Research has also shown that the SOGS has good temporal reliability ( r = 0.89 at four weeks and r = 0.67 at 12 weeks [10]).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations